2016
DOI: 10.15640/jibf.v4n2a5
|View full text |Cite
|
Sign up to set email alerts
|

Factors Influencing Payments Behavior among Customers of Islamic Retail Financing

Abstract: This paper determines factors influencing payments behavior of Islamic retail financing. By using data from 50 questionnaires, two (2) independent variables are tested to investigate the payments behavior. The factors are income per month and percentage of saving. The investigation towards the determining factors is important for the financial institutions to enhance the existing policy and procedure in credit processing and financing supervisions of Islamic retail financing.

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
1
1
1

Citation Types

0
3
0

Year Published

2017
2017
2023
2023

Publication Types

Select...
3

Relationship

0
3

Authors

Journals

citations
Cited by 3 publications
(3 citation statements)
references
References 7 publications
0
3
0
Order By: Relevance
“…This result contradicts the previous study which showed that good business performance usually can make repayment promptly. Previous studies have established that business performance has positive significant influence on the ability of the borrower to repay debt (Achim & Borlea, 2013;Nawai & Shariff, 2012;Shaharudin et al, 2016). Likewise, (Nawai, 2013) found that good business performance will more likely lead the borrower to repay the loan on time.…”
Section: Discussion Of Findingsmentioning
confidence: 93%
See 1 more Smart Citation
“…This result contradicts the previous study which showed that good business performance usually can make repayment promptly. Previous studies have established that business performance has positive significant influence on the ability of the borrower to repay debt (Achim & Borlea, 2013;Nawai & Shariff, 2012;Shaharudin et al, 2016). Likewise, (Nawai, 2013) found that good business performance will more likely lead the borrower to repay the loan on time.…”
Section: Discussion Of Findingsmentioning
confidence: 93%
“…Apart from that, Malaysia's NPL ratio had increased in September 2017 to 1.7% from 1.6% in 2016 (CEIC, 2017;World Bank Group, 2017). Among the reasons for the increase in NPL are weak global growth and economic reforms in the domestic economy such as the rationalisation of subsidies as well as the implementation of minimum wage and sales and services tax (SST) (Shaharudin et al, 2016;Wong & Eng, 2018). According to Shaharudin et al (2016) and Zhou et al (2014), the introduction of GST on 1 April 2015, SST and depreciation of the Ringgit have resulted in an increase in the cost of living, leading to adjustments in household spending.…”
Section: Introductionmentioning
confidence: 99%
“…Four variables are found to have a significant impact on SME loan repayment, namely the borrower's educational level, business experience, loan size, and repayment time. Shaharudin et al (2016) discussed the factors influencing payment behaviour with a focus on Islamic retail financing, using two independent variables, namely the level of income and the percentage of savings. They found that income level and savings have a significantly positive effect on financing repayment behaviour.…”
Section: Literature Reviewmentioning
confidence: 99%